2022
DOI: 10.33757/jik.v6i1.521
|View full text |Cite
|
Sign up to set email alerts
|

Studi Fenomenologi : Hambatan Keluarga Dalam Membawa Pasien Stroke ke Rumah Sakit

Abstract: Stroke merupakan gejala defisit fungsi susunan syaraf yang di akibatkan oleh penyakit pembuluh darah merupakan penyebab kematian tertinggi di tingkat global yaitu 55% dari 55,4 juta kematian di seluruh dunia. Data epidemiologi menunjukkan bahwa stroke menjadi penyebab kematian nomor 2 di dunia setelah penyakit jantung. Keterlambatan datang dan pasien yang tinggal sendiri menyumbang angka kematian. Kasus pasien berisiko stroke di Pariaman juga mengalami peningkatan yaitu Diabetes Melitus 15 kasus tahun 2018 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…This poses significant risks, including thrombus formation atop the plaque or plaque fragmentation, both of which may culminate in complete artery occlusion, precipitating life-threatening medical emergencies. 2 Recent studies utilizing computational fluid dynamics (CFD) and deep learning methodologies have yielded significant insights into the hemodynamic behavior in stenosed arteries and associated risks. A FLUENT simulation incorporating the Carreau model for the non-Newtonian properties of blood revealed that arterial stenosis substantially increases peak pulsatile flow pressure drop and mean wall shear stress, with minimal effect on the heat transfer coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…This poses significant risks, including thrombus formation atop the plaque or plaque fragmentation, both of which may culminate in complete artery occlusion, precipitating life-threatening medical emergencies. 2 Recent studies utilizing computational fluid dynamics (CFD) and deep learning methodologies have yielded significant insights into the hemodynamic behavior in stenosed arteries and associated risks. A FLUENT simulation incorporating the Carreau model for the non-Newtonian properties of blood revealed that arterial stenosis substantially increases peak pulsatile flow pressure drop and mean wall shear stress, with minimal effect on the heat transfer coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019 WHO also announced that the highest mortality at the global level was 55% of the 55.4 million deaths worldwide. New stroke increases can occur in 30 incidents worldwide (Yessi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%